2019
DOI: 10.1124/jpet.119.259382
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Specific Deletion of Cyclooxygenase-1 Ameliorates Dextran Sulfate Sodium–Induced Colitis in Mice

Abstract: Inflammatory bowel disease (IBD) is associated with an increased risk for thromboembolism, platelet activation, and abnormalities in platelet number and size. In colitis, platelets can extravasate into the colonic interstitium. We generated a mouse with a specific deletion of cyclooxygenase (COX)-1 in megakaryocytes/platelets [(COX-1 conditional knockout (cKO)] to clarify the role of platelet activation in the development of inflammation and fibrosis in dextran sodium sulfate (DSS)induced colitis. The disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 59 publications
(83 reference statements)
1
19
0
Order By: Relevance
“…In both human and murine platelets, the production of TXA2 is associated with COX-1 activity. COX-1 deletion in mouse platelets along with a deficiency of TXA2 highlights the role of platelet-derived TXA2 in the development of colitis and fibrosis induced by epithelial damage by inhibiting the proliferation and migration of myofibroblasts [ 102 ]. Due to the profibrotic effect of TXA2, various TP receptor antagonists have been used in antifibrosis research.…”
Section: Prostaglandinsmentioning
confidence: 99%
“…In both human and murine platelets, the production of TXA2 is associated with COX-1 activity. COX-1 deletion in mouse platelets along with a deficiency of TXA2 highlights the role of platelet-derived TXA2 in the development of colitis and fibrosis induced by epithelial damage by inhibiting the proliferation and migration of myofibroblasts [ 102 ]. Due to the profibrotic effect of TXA2, various TP receptor antagonists have been used in antifibrosis research.…”
Section: Prostaglandinsmentioning
confidence: 99%
“…Collectively our findings sustain the distinct roles of platelets beyond their fundamental participation in primary hemostasis. As previously shown in cocultures with myofibroblasts, platelet-derived TXA 2 induces morphological changes and enhances their capacity to proliferate and migrate, thus contributing to tissue fibrosis 23 . Moreover, we have shown that the interaction of platelets with colon cancer cells translates into the overexpression of COX-2, a hallmark of malignancy, and the induction of marker genes of epithelial-mesenchymal transition 21 .…”
Section: Discussionmentioning
confidence: 59%
“…Cell lysates were mixed with sodium dodecyl sulfate (SDS)(Sigma-Aldrich) sample buffer and heated to 95 °C for 5 min. Proteins (15 μg) were analyzed by SDS polyacrylamide gel electrophoresis (SDS-PAGE) 21,23 . Anti-COX-2, anti-COX-1 polyclonal antibodies (1:1000, Cayman Chemical), GAPDH polyclonal antibody (1:1000, Santa Cruz Biotechnology), or anti-β-actin polyclonal antibody (1:1000, Santa Cruz Biotechnology) were used 21,23 .…”
Section: Coculture Experiments With Human Coronary Smooth Muscle Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…In colonic mucosa, these events induce a tissue microenvironment promoting intestinal neoplasia [8]. Enhanced levels of TXA 2 activate fibroblasts, which acquire proliferative and migratory properties [38]. Moreover, plateletderived molecules can induce angiogenesis [39].…”
Section: Role Of Platelets In Early Events Of Tumorigenesismentioning
confidence: 99%